PENGARUH PIJAT OKSITOSIN MENGGUNAKAN ESSENTIAL OIL LAVENDER TERHADAP PRODUKSI ASI PADA IBU NIFAS DI DESA KEMIRI - Pratiwi, Lulu Nabillah; Nurrohmah, Anjar (STIKES Suaka Insan, 2023)
According to WHO, the prevalence of decreased milk production in postpartum women is 35.6% of women in the world. One effort that can be done to increase milk production is by oxytocin massage using lavender essential oil. This study aims to determine the production of breast milk using lavender essential oil in postpartum mothers in Kemiri Kebak Kramat Village. This type of research was a quantitative with a pre-experiment design and one group pre-test post-test design. Researchers used accidental sampling technique with a sample of 20 respondents. The research instrument used a breast milk production questionnaire. Data analysis used the Wilcoxon test. The results showed the significance value of oxytocin massage using lavender essential oil on breast milk production in postpartum mothers with a p value of 0.000 <0.05. This study shows that there is a significant effect of oxytocin massage using lavender essential oil on milk production in postpartum mothers in Kemiri Kebak Kramat Village. Keywords: Breast milk production, oxytocin massage, lavender essential oil, postpartum mother